Patterns of comorbidities differentially impact on in-hospital outcomes in heart failure patients - Veronica Murru; Elena Belfiori; Alessandro Sestu; Andrea Casanova; Carla Serra; Angelo Scuteri (BMC Geriatrics)
Abstract Background Cardiac and non-cardiac comorbidities are highly prevalent in patients with heart failure (HF). The aim of the present study was to describe their selective impact on in-hospital outcomes (length of hospitalization and mortality) of HF patients hospitalized in an Internal Medicine Unit. Methods Between January 2017 and December 2022, 12,435 (6146 F, 6289 M) inpatients were hospitalized in our Internal Medicine Unit. HF was defined according to the International Statistical Classification of Diseases and Related Health Problems (ICD) version 9 codes 428, 402.01, 402.11, 402.91, 404.11, 404.13, 404.91, 404.93. Patients were classified by burden of overall, cardiac, and of non-cardiac comorbidities (0, 1, 2, 3 +). Multivariable regression models were used to assess associations between comorbidity burden and length of stay (linear regression) or in-hospital mortality (logistic regression). Results HF patients (1481, or 11.9% of all hospitalizations during the observation period) had on average comorbidity count of 1.6. An increasing number of comorbidities was associated with longer duration of hospitalization and mortality. Non-cardiac, but not cardiac, comorbidities were associated with significantly higher length of stay (beta coefficient 2.86 ± 0.27) and in-hospital mortality (OR 1.90, 95% confidence interval (CI) 1.60–2.23; p < 0.0001). Conclusions Cardiac and non-cardiac comorbidities differentially impact on in-hospital outcomes of older HF patients hospitalized in an Internal Medicine unit. Their more precise management will allow a reduction of avoidable hospitalization in HF patients.